PENGARUH VARIASI KONSENTRASI GULA PASIR PADA PEMBUATAN SUWAR SUWIR DARI TAPE SUKUN TERHADAP PENERIMAAN KONSUMEN - Nugerahani, Ira; Suprijono, Maria Matoetina; Lianawati, Lianawati (Jurnal Teknologi Pangan dan Gizi, 2004)
"Suwar-suwir" is an intermediated moisture food commonly produced from traditional fermented cassava and it is very famous in East Java. In some areas "suwar-suwir" is made of fermented breadfruit ("tape sukun"). Suwar-suwir prepared by adding cane sugar to the fermented cassava and heating it, and then dehydrating. The addition of high concentration of cane sugar caused crystallization due to heating, and this influenced the sensory properties of the products. Finding the proper concentration of cane sugar should solve this problem. A Randomized Group Design was determined with a single factor i.e. concentration of cane sugar consist of six levels concentration as follows: 80%, 90%, 100%, 120% and 130%, respectively. The parameters including appearance, hardness, and taste were measured. The research result showed that there was significantly among treatments to all parameters. "Breadfruit Suwar-suwir" contains 100% of cane sugar was the best product.